The jeune école : the strategy of the weak - Roksund, Arne (History of warfare, 2007)
The jeune acole represents a school of maritime strategy dealing with the dilemmas of the weaker power. This book presents a fresh interpretation of the jeune acole based on primary sources. This French body of naval thought is distinguished from other strategies of the weak by its elaborate prescriptions for the offensive use of naval forces.